1986
DOI: 10.1111/j.1745-4557.1986.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid and Riboflavin Content of Asparagus During Marketing

Abstract: California-grown asparagus purchased from wholesale markets and retail stores in the greater New York area 6 to 9 days afer harvest, and Calijornia asparagus purchased at retail stores in the greater New York area then stored 3 days at 5.5 "C and 90-95% relative humidity to simulate consumer holding were analyzed for total ascorbic acid (AA), L-ascorbic acid, dehydroascorbic acid (DHAA) and riboflavin content. Asparagus from wholesale markets, retail stores and storage averaged 15, 10, and 9mg AA/IOOg freshwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
11
0
4
Order By: Relevance
“…The higher K values after storage were probably due to product shrinkage (water loss). Hudson et al 1985, in New Jersey, showed that ascorbic acid and thiamine levels in locally grown strawberries were lower than those shipped from either Florida or California. The generally higher mineral element content of western grown strawberries and grapes found in the present study may suggest differences in soil, fertility, and other management practices or product shrinkage in transit.…”
Section: **mentioning
confidence: 94%
“…The higher K values after storage were probably due to product shrinkage (water loss). Hudson et al 1985, in New Jersey, showed that ascorbic acid and thiamine levels in locally grown strawberries were lower than those shipped from either Florida or California. The generally higher mineral element content of western grown strawberries and grapes found in the present study may suggest differences in soil, fertility, and other management practices or product shrinkage in transit.…”
Section: **mentioning
confidence: 94%
“…annuum) are one of the favorite crops for domestic market and export. On the other hand, peppers are highly perishable products, in particular during the postharvest life, high losses can occur due to fungal decays and senescence (Hudson et al, 1985). The development of fungi during postharvest transport and storage of horticultural products can cause great economic losses (Marquenie, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…El contenido total de ácido ascórbico depende de la variedad y es afectado por diversos factores: Es susceptible a la degradación en presencia de luz y oxígeno y a la actividad enzimática interna, la que se presenta en el tejido interno de la fruta cuando ésta sufre cortaduras y magulladuras. Es afectado por la temperatura, la humedad, la acidez, ya que los ácidos regulan el pH celular y pueden influir en la apariencia de los pigmentos dentro de la fruta y finalmente también se ve afectado por el grado de maduración (Hudson y Mazur, 1985), así como por las condiciones entre la cosecha y el consumo; las temperaturas durante el transporte y por las diferencias entre las áreas de crecimiento y las estaciones.…”
Section: Parámetros O Atributos De Calidad De La Fresaunclassified
“…En el caso de la Camarosa aunque no fue significativa (p = 0.1200) si hubo una diferencia notable entre los contenidos de vitamina C en las fresas provenientes de las tres etapas del manejo. Este descenso posiblemente sea debido a la sensibilidad de este compuesto a varios factores como la luz, el oxígeno y la temperatura como lo han mencionado Hudson y Mazur (1985). Las altas temperaturas que prevalecieron en el campo y durante el manejo (de hasta 32°C) debieron ser las causas de su pérdida.…”
Section: Contenido De áCido Ascórbico (Vitamina C)unclassified
See 1 more Smart Citation